ANALISIS PRAKTIK WIRAUSAHA PADA USAHA MERCON TANTAN SEBAGAI UMKM KULINER LOKAL - Anisa Auliya; Risti Indah Sari F; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze entrepreneurial practices in local culinary Micro, Small, and Medium Enterprises (MSMEs), namely Mercon Tantan, amidst the rapid development of the food industry in Indonesia. MSMEs are the main foundation of the national economy with a significant contribution to job creation and economic growth. Mercon Tantan is a manifestation of innovation that raises the theme of the typical spicy dish